A cross-sectional study of the relative availability and prominence of shelf space allocated to healthy and unhealthy foods in supermarkets in urban Ireland, by area-level deprivation - S. O'Mahony; N. Collins; G. Doyle; A. McCann; K. Burke; A. Moore; E. R. Gibney (BMC, 2024)
Abstract Background Diet-related noncommunicable diseases (NCDs) are a leading cause of ill-health and death across Europe. In Ireland, dietary intakes of saturated fat, free sugar and salt exceed World Health Organization recommendations, and excess consumption follows a social gradient increasing population risk of diet-related NCDs. The retail food environment can influence consumer food choice and subsequent dietary intakes. In high income countries, supermarkets are an increasingly influential actor in consumer food availability, choice, purchase, and subsequent food intake. This study aims to assess the relative availability and prominence of healthy and unhealthy foods in Irish supermarkets, by area-level deprivation. Methods This study used a cross-sectional study design, and applied a validated measure, as described in the INFORMAS Protocol: Food Retail - Food availability in supermarkets. Between October 2021 and February 2022, shelf space (m2) (height or depth (cm) × length (cm)) and prominence (visibility), of foods, classified as healthy and unhealthy and represented by a proxy indicator, were collected in supermarkets (n = 36) in County Dublin, Ireland. Overall the proportion of mean relative shelf space (m2), allocated to healthy and unhealthy foods, and its prominence, by area-level deprivation, and retailer, were determined. We used t-tests and one-way ANOVA to analyse possible differences between the proportion of relative shelf space available to healthy and unhealthy foods, and its prominence, by area-level deprivation and retailer. Results The study found the proportion of shelf space measured allocated to unhealthy food was 68.0% (SD 10.6). Unhealthy foods were more likely to be in areas of high prominence. Overall, there was no statistically significant difference between the proportion of relative shelf space available to unhealthy foods in areas of high and low deprivation. A statistically significant difference in the proportion of relative shelf space allocated to healthy and unhealthy food by area level deprivation was found in one retailer. Conclusion Unhealthy foods had a higher proportion of shelf space and were more prominent than healthy foods in supermarkets in County Dublin, Ireland. The current availability and prominence of foods in supermarkets does not align with Food Based Dietary Guideline recommendations and does not support consumers to make healthier food choices. There is a need for supermarkets in Ireland to improve the availability and prominence of healthy foods to support consumers to make healthier food choices.